(untitled) (Journal of the College of Basic Education, 2024)
The study aimed to investigate the relationship between social and psychological pressures and psychological resilience among working women in Tubas Governorate. The researcher used the correlational descriptive approach and employed a questionnaire to collect data from a sample of (40) working women in both public and private sectors in Tubas Governorate, selected through purposive sampling. The study yielded the following results:  The average level of social pressures among working women in Tubas Governorate was moderate, with a mean of (3.19).  The average level of psychological pressures among working women in Tubas Governorate was high, with a mean of (3.63).  The average level of psychological resilience among working women in Tubas Governorate was moderate, with a mean of (2.67).  There was a statistically significant relationship (at α≤0.05 level) between social pressures and psychological pressures among working women in Tubas Governorate, which was positive and accounted for (62.3%).  A statistically significant relationship (at α≤0.05 level) was found between social pressures and psychological resilience among working women in Tubas Governorate, which was negative (-0.319).  A statistically significant relationship (at α≤0.05 level) existed between psychological pressures and psychological resilience among working women in Tubas Governorate, which was negative (-0.512).  There were no statistically significant differences (at α≤0.05 level) in the levels of social pressures, psychological pressures, and psychological resilience among working women in Tubas Governorate based on variables such as age, marital status, educational level, and sector type. The study recommended that social institutions and organizations supporting women’s rights raise awareness about the importance of women’s work and its impact on families to reduce negative perceptions about women’s work. It also suggested that employers in Tubas Governorate ensure gender equality at the workplace without discrimination in rights and duties between men and women.